Analisi Bahasa Kiasan dalam lirik lagu Feel Good Inc. dan Clint Eastwood oleh Gorrilaz - Ula Nisa El Fauziah (ELT in Focus, 2022)
This study entitled "An Analysis of Figurative Language in Feel Good Inc and Clint Eastwood Song Lyrics by Gorillaz" has two objectives. The first is to find out the meaning that Gorillaz wants to convey through the song Feel Good Inc and Clint Eastwood, and the second is to find out the types of figures of speech contained in the Gorillaz song lyrics. The data used for this analysis are the lyrics of the Gorillaz song entitled "Feel Good Inc" and "Clint Eastwood". The qualitative descriptive method was used in this study. The data obtained were then analyzed by separating each sentence to get contextual meaning and assisted by a dictionary. The types of speech were found: metaphor, hyperbola, allusion, simile, and personification. The most figurative language in the song is hyperbole. Three lyrics contain hyperbole, two personifications, one metaphor, two similes, and two allusions. Based on the contextual understanding of Gorillaz's song, Feel Good Inc. Gorillaz wants to convey criticism of Feel Good Incorporated, a consumerism crime company in which the workers are locked up and unable to get out. This song also describes people who are fed up with the evil that has happened for so long that people want to make a revolution for a better life. Then, in the song "Clint Eastwood" Throughout the entire song, several words are mentioned related to disorders and conditions such as schizophrenia, a condition in which reality is convoluted, and the person is unable to think and act clearly, as well as psychosis, which is far away. Keywords: Contextual Meaning, Figurative Language, Song Lyrics.